1978
DOI: 10.1002/hlca.19780610202
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Structure of Cubane (C8H8) as Revealed by Photoelectron Spectroscopy

Abstract: SummaryHigh resolution He (Ia) and He (IIa) photoelectron spectra of cubane are reported. The assignments of the bands to different states of the cubane radical cation are made on the basis of ab initio STO-3G and MIND0/3 calculations, using geometries optimized within each treatment. The vibrational fine-structure observed supports the proposed assignment. An open shell MIND0/3 model for ground state cubane radical cation suggests that the Jahn-Teller distorted system fluctuates between twelve equivalent stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…The spectra also clearly indicate the 's-like' and 'p-like' nature of the respective orbitals studied. The binding energy spectrum at φ = 0 + 10 • is qualitatively similar to the corresponding PES spectrum (Bischof et al 1978). Figs 12 and 13 show our theoretical PWIA-DFT momentum distributions for the two outermost valence (degenerate) orbitals of cubane (2t 2g , 1t 2u ) and our corresponding experimental momentum distributions, as derived from our binding energy spectra.…”
Section: Ethylene Oxidesupporting
confidence: 58%
“…The spectra also clearly indicate the 's-like' and 'p-like' nature of the respective orbitals studied. The binding energy spectrum at φ = 0 + 10 • is qualitatively similar to the corresponding PES spectrum (Bischof et al 1978). Figs 12 and 13 show our theoretical PWIA-DFT momentum distributions for the two outermost valence (degenerate) orbitals of cubane (2t 2g , 1t 2u ) and our corresponding experimental momentum distributions, as derived from our binding energy spectra.…”
Section: Ethylene Oxidesupporting
confidence: 58%
“…The corresponding splitting of the ionization energies with the assigned MOs (DI n )r epresents the degree of interaction. Initial studies on cubane, [95] cubane derivatives, [96] and BCO derivatives [97] showedo nly very small splitting, characteristics for only av ery feeble interaction of the linked systems. Ad ifferent picture was observed for BCP derivatives.…”
Section: Electronic Communicationmentioning
confidence: 99%
“…From the analysis of the bond interaction strength in linear and cyclic hydrocarbons, Bischof et al 70 showed that the magnitude of the C-C bond interaction strength increased from 2.9 to 4.8 eV with a decrease in the associated bond angle from 109.5 to 60°. In the case of cage structures, such as CUB, analysis of the photoelectron spectrum together with theoretical calculation have shown 70 a direct relationship between bond angles and bond interaction strength.…”
Section: Dependence Of V Ab On the Cage Structurementioning
confidence: 99%